Exploring sourcing patterns during the Covid-19 pandemic: A ‘lived experience’ perspective - Spyridou, Lia Paschalia; Vatikiotis, Pantelis; Maniou, Theodora (My University, 2022)
When crises occur, people experience an increasing need for information and sense-making (Lowrey, 2004). The plurality, depth and credibility of the information conveyed by the media shapes public understanding and knowledge (Cushion, Morani, Kyriakidou & Soo, 2021). In the case of the coronavirus pandemic people used newsmedia to understand the disease itself, be aware of preventive steps taken by governments, comprehend the benefits and risks of proposed medical measures (Fletcher, Kalogeropoulos, Simon & Nielsen, 2020). Relevant work indicates that apart from being a health emergency, the Covid-19 pandemic comprises a communication crisis; misinformation and conspiracy theories were on the rise (Cushion et al, 2021), press freedom was constrained (Papadopoulou & Maniou, 2021), the economic and labour situation of many news outlets worsened (Nielsen, Cherubini & Andi, 2020; Posetti, Bell & Brown, 2020), while negative reporting emphasing statistics of infected and deceased, (Ytre-Arne & Moe, 2021) made people feel overwhelmed and switch off from the news (Nguyen et al., 2021). Despite growing literature on news media and the pandemic, less attention has been given to the sourcing practices and (emerging) values which shaped news production around Covid-19. The consequences of how journalists use sources is an enduring object of communication research; the question of who has voice and authority in mediated constructions of reality remains central when interrogating journalistic representations (Gans, 1979; Tuchman, 1978; Zelizer, 1990). Additionally, sourcing patterns are part and parcel of journalism’s claim to truthfulness (Curran, 2019). To address this gap, this study focuses on the sourcing practices of journalists to collect and verify information. Drawing upon literature on sourcing practices and Hall et al’s (1978) framework on primary definers and using 30 semi-structured interviews with journalists in Greece and Cyprus, the study goes beyond the mere identification of the types of sources used, to shed light on the factors which shaped professionals’ sourcing practices, the perceived effects of these practices on storytelling and how journalists evaluate their performance. The study contributes empirically to what Lewis (2020) calls the ‘lived experience of news production’ during the coronavirus crisis suggesting that journalism scholars should consider the complexity of the crisis, the trauma and psychological toll of covering a debilitating crisis with few resources amid pay cuts and layoffs.
Keywords: News production